"Por uma religião nacional": a separação entre Igreja e Estado e a disputa religiosa entre católicos e protestantes em Belém do Pará (1889-1931) - Gama, Rafael da (2019)
In this research, we will try to look into Christianity in Belém do Pará from the religious dispute of its main aspects in the city: Catholicism and Protestantism. The selected time (1889-1931) is significant because it has as a milestone the end of the empire and the beginning of the First Republic in Brazil and, consequently, the official separation of the Catholic Church from the Brazilian State. With this, we note that Catholics and Protestants structure their discourses and religious practices influenced by this new political moment that begins. Through the analysis of periodicals, means of the great communication like books and records of memory produced in the period, we will analyze the religious dispute between Catholics and Protestants in the city, which took great proportions from the symbolic field to the physical one, in a conjuncture of separation between Church and State in the new political regime represented by the republican regime. We will try to analyze a specific religious dynamic present in Belém do Pará, with its majority Catholicism and a fervent devotion to the Virgin of Nazareth. A minority Protestantism, but better consolidated in the city and always acting as active agents, whether religious, social or political, and the beginning of the Pentecostal movement that emerged in the period, as a side of Protestantism that brought with itself supernatural elements that managed to dialogue with the Catholicism that was popular in the region. In this specific political-religious scenario, Catholics and Protestants reveal quarrels among themselves that go beyond clashes on the theological level, showing us a dispute for the recognition of being seen as the main religions of the nation. In a political formation of absence from an official religion, Catholics and Protestants seek to represent themselves as salvific solutions not only in the religious sphere, but as important elements for the country's prosperity, dialoguing with a political discourse and thus seeking to be recognized by the State and by society as the true national religions